Integration of Alcohol Use Disorder Interventions in General Health Care Settings in Sub-Saharan Africa: A Scoping Review - Mushi, Dorothy; Francis, Joel M.; Moshiro, Candida; Hanlon, Charlotte; Teferra, Solomon (Frontiers in Psychiatry, 2022)
Integration of alcohol use disorder interventions in general health care settings in sub-Saharan Africa: A scoping review Abstract Introduction Alcohol use disorder (AUD) is among the leading cause of morbidity and mortality in sub-Saharan Africa. Despite this, AUD is often not detected in health care settings, which contributes to a wide treatment gap. Integrating services for mental, neurological and substance use disorders in general health care settings is among the recommended strategies to narrow this treatment gap. This scoping review aimed to map the available evidence on integration of AUD interventions in general health care settings in sub–Saharan Africa. Methods We searched four databases (PubMed, PsycINFO, CINAHL and Africa Wide Information) for publications up to December 2020. The search strategy focused on terms for alcohol use, alcohol interventions and sub-Saharan African countries. Studies that reported AUD interventions in general health care settings in sub–Saharan Africa were eligible for inclusion. Over 3817 potentially eligible articles were identified. After removal of duplicates, 56 articles were included for a full article review. Of these, 24 papers reporting on 22 studies were eligible and included in a narrative review Results Of the 24 eligible articles, 19 (80%) provided a description of AUD interventions that were being delivered in general health care settings, 3 (12%) described plans or programs for integrating AUD interventions at different levels of care, including in health facilities, and 2 (8%) studies reported on AUD interventions integrated into general health care settings. Conclusions This review shows that there is limited evidence on the integration of AUD interventions in health care settings in sub-Saharan Africa. There is an urgent need for studies that report systematically on the development, adaptation, implementation and evaluation of integrated AUD interventions in health care settings in sub-Saharan Africa. Keywords: Integration, alcohol use disorder, interventions, general health care, sub–Saharan Africa